2016
DOI: 10.1016/j.bjm.2016.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the variable region in the class 1 integron of antimicrobial-resistant Escherichia coli isolated from surface water

Abstract: Fecal bacteria are considered to be a potential reservoir of antimicrobial resistance genes in the aquatic environment and could horizontally transfer these genes to autochthonous bacteria when carried on transferable and/or mobile genetic elements. Such circulation of resistance genes constitutes a latent public health hazard. The aim of this study was to characterize the variable region of the class 1 integron and relate its genetic content to resistance patterns observed in antimicrobial-resistant Escherich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 43 publications
2
21
0
Order By: Relevance
“…It has been reported that integrons carrying antimicrobial resistance gene cassettes were highly prevalent in aquatic environment ( Guo et al, 2011 ; Canal et al, 2016 ). Moreover, Class 1 integrons have been reported widely in Gram-negative bacteria which were responsible for both the spread and increase of antimicrobial resistance throughout the world ( Koczura et al, 2013 ; Canal et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that integrons carrying antimicrobial resistance gene cassettes were highly prevalent in aquatic environment ( Guo et al, 2011 ; Canal et al, 2016 ). Moreover, Class 1 integrons have been reported widely in Gram-negative bacteria which were responsible for both the spread and increase of antimicrobial resistance throughout the world ( Koczura et al, 2013 ; Canal et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that integrons carrying antimicrobial resistance gene cassettes were highly prevalent in aquatic environment ( Guo et al, 2011 ; Canal et al, 2016 ). Moreover, Class 1 integrons have been reported widely in Gram-negative bacteria which were responsible for both the spread and increase of antimicrobial resistance throughout the world ( Koczura et al, 2013 ; Canal et al, 2016 ). Our analysis also revealed that Class 1 integrons were common in E. coli isolates of river Yamuna (50%), more than those reported from strains isolated from Malaysia (21%) ( Ghaderpour et al, 2015 ), France and Portugal (11%) ( Laroche et al, 2009 ; Pereira et al, 2013 ), and Czechia (15%) ( Dolejská et al, 2009 ).…”
Section: Resultsmentioning
confidence: 99%
“…All the array types reported in this study have been previously reported in the literature. Array types 1 and 3 in particular have been reported widely in bacteria from human clinical sources, aquaculture, farm animals, rivers and hospital wastewater in Nigeria and Ghana [29,72,73], Central African Republic [74], Egypt [75], Europe [76][77][78][79][80][81][82][83], China [84][85][86], Brazil [87], Canada [54] and US [88]. The Type 1 cassette (dfrA7) was found associated with a widely disseminated Tn21-type transposon in Nigeria and Ghana [72].…”
Section: Characterisation Of Integrons Gene Cassettesmentioning
confidence: 99%
“…The main factor in the emergence of multidrug-resistance (MDR) strains is the ability of bacteria to gain and disseminate exogenous genes through mobile genetic elements [ 4 ]. The upgrowth of E. coli isolates with MDR phenotypes has been formerly reported and may extend from one ecosystem to another by lateral gene transfer; integrons [ 5 ].…”
Section: Introductionmentioning
confidence: 99%